Suppressed Emotions of Asian Americans in Beef: A Pragmatic Analysis - Fadhilah Azizah Hasan; Harwintha Yuhria Anjarningsih (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2025)
The series Beef (Lee, 2023) offers a unique perspective on Asian American emotions by featuring two vengeful characters who challenge traditional notions of emotional restraint. This study investigates their anger, linking it to suppressed emotions arising from their experiences in a racially hierarchical society. Utilizing discourse and pragmatic analysis, the paper examines how these repressed emotions reflect broader societal identities. Key scenes demonstrate that the characters frequently violate conversational norms to align with social expectations, hide less desirable traits, and project a competent image. This behaviour not only masks their true feelings but also heightens their frustration. The study also highlights that those around them use similar strategies to steer conversations towards specific goals. Ultimately, the paper argues that the characters’ departure from conversational norms is a strategic attempt to assimilate into American society while managing their repressed emotions.